How the Notion of “Knowledge Rich Context” Can Be Characterized Today - Condamines, Anne (Frontiers in Communication, 2022)
This paper studies how the notion of Knowledge Rich Contexts (KRCs), initially defined as passages of text allowing access to elements that define terms, has evolved. It discusses related work in Natural Language Processing (NLP), which has led to disciplinary convergence. It mainly presents the way in which KRCs can manifest themselves within a corpus, in the form of explicit or implicit markers and lexico-syntactic or morphological markers. Extra-linguistic elements are examined through the study of the domain and the textual genre of the corpus studied, and by the adaptation of KRCs to a particular demand (evolution in time, interdisciplinarity...). All types of functioning are illustrated with real data from different corpus-based studies. The study of the notion of KRC allows us to address fundamental questions in the linguistic study of specialized texts, such as the link between form and meaning and between linguistic and extra-linguistic contexts.